Preparation method of high-toughness heterogeneous configuration composite material and TiBw / TC4 composite material
Through low-energy ball milling and vacuum hot pressing or discharge plasma sintering, a high-strength and tough heterostructure TiBw/TC4 composite material was prepared, solving the contradiction between high strength and tough plasticity of titanium-based composite materials, and achieving efficient, economical and environmentally friendly preparation of the material.
Patent Information
- Application Number
- CN202411685078.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-04-04
AI Technical Summary
Titanium-based composite materials are difficult to take into account good toughness and plasticity while pursuing high strength. Traditional strengthening methods are likely to lead to the inversion of strength-plasticity.
Using a low-cost, simple and controllable preparation method, the enhanced phase source is embedded on the surface of the titanium substrate through two-step low-energy ball milling treatment, and a high-strength heterostructure TiBw/TC4 composite material is formed during vacuum hot pressing or discharge plasma sintering.
The high strength and high plasticity matching of titanium-based composite materials is achieved, the process flow is simplified, the cost is reduced, and the comprehensive mechanical properties of the material are improved.
Smart Images

Figure CN119753408A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of titanium-based composite materials, in particular to a titanium-based composite material with a heterogeneous configuration and a preparation method thereof. Background Art
[0002] In recent years, there has been an urgent need for lightweight, high-strength and high-toughness structural materials in aerospace fields such as space shuttles and launch vehicles. Titanium alloys have excellent properties such as high specific strength, high temperature resistance and corrosion resistance, and have important application prospects in aerospace, chemical industry, nuclear industry and other fields. However, insufficient strength as a structural material has become the biggest obstacle to the widespread application of titanium alloys.
[0003] At present, introducing ceramic reinforcement phase into metal materials to prepare metal matrix composites is an effective way to strengthen metals. Titanium matrix composites have different degrees of improvement in strength, stiffness, operating temperature, corrosion resistance, etc. compared with single titanium and titanium alloy matrix, and are more widely used in key load-bearing components than titanium and titanium alloy matrix.
[0004] Powder metallurgy has important applications in the preparation of titanium-based composites due to its advantages such as simple process, low cost and excellent near-net formability. From the Hashin-Shtrikman (HS) theory, it can be seen that the strength and elastic modulus of titanium-based composites with uniformly distributed reinforcement phases are close to the theoretical lower limit, while the strength and elastic modulus of titanium-based composites with non-uniformly distributed reinforcements are close to the theoretical upper limit. Therefore, discontinuous titanium-based composites reinforced with in-situ self-generated ceramic particles are considered to be titanium-based composites with great development potential due to their higher theoretical strength and lower cost. In particular, composites with TiB2 as reinforcement and TC4 dual-phase titanium alloy as matrix. Due to the excellent comprehensive mechanical properties of TC4 itself, and the reaction of TC4 with TiB2 generated by in-situ reaction, the strength and elastic modulus of titanium-based composites are close to the theoretical upper limit. w The thermal expansion coefficients are similar, the comprehensive mechanical properties of the composite material are more outstanding, and the organization has stronger stability.
[0005] Huang et al. first reported a TiB with a network structure w / TC4 composite material (Scr.Mater, 2009, 60:996-999), in which the in-situ self-generated TiB w A quasi-continuous three-dimensional network distribution is formed around the TC4 particles, and TiB w There is also a symbiotic structure between them, forming branches, which has a good effect on the transfer of loads. Therefore, based on the above reasons and the research reports of relevant scholars, the composite materials with uneven reinforcement prepared by powder metallurgy + in-situ reaction have gradually become one of the research hotspots in the field of titanium-based composite materials.
[0006] In recent years, with the deepening of relevant research and its close integration with actual production, the development of titanium-based composite materials has encountered a new bottleneck, that is, metal structural materials need to have good toughness and plasticity while pursuing high strength. From the perspective of strengthening and toughening mechanism, traditional strengthening methods, such as solid solution strengthening, deformation strengthening, nano-strengthening, dispersion strengthening, etc., can greatly improve the strength of titanium alloys, but will produce strength-plasticity inversion problems. On the one hand, the strengthening of materials requires hindering the movement of dislocations, pinning dislocations, and even entanglement of dislocations. On the other hand, the improvement of material plasticity requires mobilizing dislocations, absorbing strain energy, and delaying deformation and cracking. From this point of view, the strengthening and toughening of metal structural materials seem to be an irreconcilable contradiction.
[0007] Traditional strengthening and toughening mechanisms seem unable to overcome the above contradictions. In 2015, Wu et al. were inspired by the microstructures of bamboo, shells and other organisms and creatively proposed the design concept of heterogeneous configuration (PNAS, 2015, 112(47): 14501). The design of heterogeneous configuration can overcome the problem of strength-plasticity mismatch, and form microscopic heterogeneous structures in the organization through differences in grain size, crystal structure or material composition and content, thereby improving the comprehensive mechanical properties of the material.
[0008] Specifically, titanium-based composite materials with heterogeneous configurations will produce great strain incompatibility between soft and hard units during material deformation. A large number of geometric dislocations are accumulated at the interface of the soft and hard units, and a stress / strain gradient is generated at the interface, which in turn generates back stress. The existence of back stress causes the interface to undergo work hardening and improves the strength of the material. At the same time, back stress can also delay the necking process and improve the plasticity of the material, ultimately enabling the material to obtain excellent comprehensive mechanical properties with matching strength and toughness. The design concept of heterogeneous configuration has opened up a new path for the further development of strengthening and toughening of titanium-based composite materials.
[0009] At present, some reports have been published on the research of heterogeneous titanium-based composite materials. The Chinese patent with the authorization announcement number CN112647029B discloses a three-dimensional pellet composite structure TiB reinforced TMCs and its preparation method, which introduces the preparation of TiB in the form of pellets by ball milling a mixed powder of titanium and TiB2 (titanium boron powder) and aluminum powder, and then spark plasma sintering. w / Ti composite material. This method densifies the composite material by taking advantage of the low melting point and fluidity of aluminum during the sintering process. After sintering, the TiB2 in the original titanium boron powder is distributed in the matrix in a three-dimensional pellet structure. This method has a fracture strain of 6.3% while ensuring a tensile strength of 980.5MPa.
[0010] Furthermore, the Chinese patent with the authorization announcement number CN112695262B discloses a titanium alloy-based composite material with a microstructure and a preparation method thereof, which introduces the preparation of TiB in the form of pellets by mixing titanium boron powder with aluminum powder and vanadium powder and then ball milling the mixture through spark plasma sintering. w / TC4 composite material. Compared with the aforementioned Chinese patent with authorization announcement number CN112647029B, the matrix in the composite system changes from a single α phase to an α+β dual-phase structure, the material tensile strength reaches 1070MPa, and the fracture strain reaches 11.9%.
[0011] In summary, the above two methods make TiB in composite materials w The titanium boron powder is distributed in a pelletized form, thus realizing the heterogeneous design of the reinforcement. However, in the above method, the original titanium boron powder is prepared by an aerosol method, which is a complicated process and the preparation cost of the composite material is high.
[0012] In addition to the heterogeneous configuration design of the reinforcement, the Chinese patent with the authorization announcement number CN111961902B discloses a titanium-based composite material with a heterogeneous structure and its preparation method and application, which also introduces the heterogeneous configuration design of the titanium or titanium alloy matrix. This method mixes the reinforcement powder such as nano-scale diamond or micron-scale titanium diboride with a small amount of fine matrix powder, adds it to the coarse-grained matrix powder of the main body, and synthesizes TiB in situ through spark plasma sintering. w The difference in the size of TiC particles, coarse grains and fine grains, and the distribution of reinforcements make the titanium-based composites present dual heterogeneity in grain size and composition.
[0013] However, after the introduction of nano-scale powders in this method, powder agglomeration is more serious, and organic solvents are required for ultrasonic dispersion and as lubricants for ball milling, and the process is more complicated. In addition, the use of high-energy ball milling technology also leads to high energy consumption in the material preparation process. Furthermore, this method only conducts uniaxial compression tests on the prepared composite materials, while the tensile performance test, which is more important for showing the strength and plasticity of the composite materials, is not reflected, which to a certain extent limits the engineering evaluation of its comprehensive mechanical properties.
[0014] Therefore, in order to expand the application scenarios of titanium-based composites and enable titanium-based composites to have high strength while having more matched plasticity and toughness, it is necessary to further develop and research high-strength and toughness titanium-based composites with heterogeneous structures prepared through simple, controllable and low-cost processes. Summary of the invention
[0015] The purpose of the present invention is to avoid the shortcomings of the prior art and provide a method for preparing a high-strength and high-toughness heterogeneous composite material with low cost, simple preparation method, high strength and high plasticity and toughness, and a TiB w / TC4 composite material.
[0016] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a high-strength and tough heterogeneous composite material, wherein the composite material is formed by titanium or titanium alloy as a titanium matrix and one or two of in-situ self-generated titanium carbide and titanium boride as a reinforcing phase; the method for preparing the titanium-based composite material comprises the following steps:
[0017] A mixed powder of 1-3wt.% of reinforcing phase source powder and 97-99wt.% of titanium fine-grained matrix powder with a powder size of 1-45μm is subjected to at least one unidirectional non-stop low-energy ball milling process for 6-10 hours at a rotation speed of 180-220r / min to embed the reinforcing phase source into the surface of the titanium matrix to obtain a reinforcing phase source / titanium fine-grained matrix composite powder;
[0018] Next, a titanium coarse-grained matrix powder with a mass percentage of 5 to 30 wt.% and a powder size of 120 to 280 μm is added to the reinforcing phase source / titanium fine-grained matrix composite powder, and a one-way non-stop low-energy ball milling treatment is performed at least once for 1 to 4 hours at a rotation speed of 80 to 120 r / min to ensure the sphericity of the coarse-grained and fine-grained matrix powders while uniformly dispersing the coarse-grained matrix powder to obtain a reinforcing phase source / titanium fine / coarse-grained matrix composite powder;
[0019] Finally, the composite powder of the reinforcement phase source / titanium fine / coarse grain matrix is subjected to vacuum hot pressing sintering or spark plasma sintering in a mold. After sintering, the mold is opened to obtain the high-strength and toughness heterogeneous reinforcement phase / titanium matrix composite material.
[0020] Furthermore, in the unidirectional non-stop low-energy ball milling process, stainless steel grinding balls with a diameter of 5 to 10 mm are used, and the ball-to-material ratio in the two ball milling processes is 3:1 to 5:1.
[0021] Furthermore, the mold is a graphite mold with a compressive strength greater than 60 MPa.
[0022] Furthermore, after the composite powder is loaded into the mold, cold pressing is performed at 5 to 15 MPa for 0.5 to 4 hours to make the composite powder dense and air-free, the powder is not easily oxidized, and the subsequent sintering and pressurizing process will be more stable.
[0023] Furthermore, the vacuum hot pressing sintering is a process in which the composite powder in the mold is subjected to at least three-stage heating treatment from room temperature to 1100-1200°C at a pressure of 10-35MPa, a temperature of 1100-1200°C, and a heating rate of 5-10°C / min, and finally the powder is kept warm and pressurized for 0.5-2h and then cooled and unloaded in the furnace.
[0024] Furthermore, the three-stage heating process of the vacuum hot pressing sintering is specifically as follows:
[0025] First, heat from room temperature to 500-600°C, and keep at 500-600°C for 10-15 minutes;
[0026] Secondly, heat from 500-600℃ to 900-1000℃, and keep at 900-1000℃ for 10-15min.
[0027] Finally, heat from 900-1000℃ to 1100-1200℃, and keep at 1100-1200℃ for 0.5-2h, and cool with the furnace after heating;
[0028] At the same time, during the three-stage heating process, when the temperature rises to 500-600°C, the pressure is increased to 30-40% of the maximum pressure, when the temperature rises to 900-1000°C, the pressure is increased to 70-80% of the maximum pressure, and when the maximum temperature reaches 1100-1200°C, the pressure is increased to the maximum pressure of 10-35MPa. After maintaining the pressure, the furnace is cooled and unloaded.
[0029] Furthermore, the spark plasma sintering is a process of at least three-stage heating of the composite powder in the mold under the conditions of a pressure of 20-50 MPa, a temperature of 1000-1200°C, and a heating rate of 20-100°C / min, and finally heat preservation and pressure maintenance for 0.2-1h and then cold unloading with the furnace.
[0030] Furthermore, the three-stage heating process of the spark plasma sintering is specifically as follows:
[0031] First, heat from room temperature to 500-600°C, and keep at 500-600°C for 5-10 minutes;
[0032] Secondly, heat from 500-600℃ to 800-900℃, and keep at 800-900℃ for 5-10min.
[0033] Finally, heat from 800-900℃ to 1000-1200℃, and keep at 1000-1200℃ for 0.2-1h, and cool with the furnace after heating;
[0034] At the same time, during the three-stage heating process, the pressure is increased to 30-40% of the maximum pressure when the temperature rises to 500-600°C, and to 70-80% of the maximum pressure when the temperature rises to 800-900°C. When the maximum temperature reaches 1000-1200°C, the maximum pressure is increased to 20-50MPa. After maintaining the pressure, the furnace is cooled and unloaded, and the sintering atmosphere is vacuum.
[0035] Furthermore, the reinforcing phase source is titanium diboride powder, the matrix is TC4 fine crystal and coarse grain powder, and the obtained composite powder is a composite powder of TiB2 / TC4 titanium fine / coarse grain matrix. The final composite material is a high-strength and tough heterogeneous TiB w / TC4 composite material; the particle size of the TiB2 is 0.5μm, the fine grain size of the TC4 powder is 1 to 25μm, the coarse grain size of the TC4 powder is 100 to 150μm, the TiB w It is in-situ self-generated titanium boride whisker.
[0036] The present invention also provides a high-strength and tough heterogeneous TiB obtained by the preparation method. w / TC4 composite material, the TiB w The / TC4 composite material has a heterogeneous structure of TC4 coarse-grained region and TC4 fine-grained region. w It is a self-produced product of the in-situ reaction of TiB2 and TC4; the reinforcing phase TiB w It is dispersed and evenly distributed in the fine-grained area, distributed at the grain boundaries and inside the grains in the fine-grained area, distributed in discontinuous rings at the boundaries of the coarse-grained area, and the coarse-grained area is evenly distributed on the fine-grained matrix, showing an obvious bimodal heterogeneous configuration.
[0037] The beneficial effects of the present invention are:
[0038] The ball milling process of the present invention does not require the addition of any ball milling aid, reduces element pollution, and the micron-level original powder has no obvious agglomeration phenomenon. No organic solvent ultrasonic dispersion is required before ball milling, and no sintering exhaust is required subsequently, which simplifies the process, reduces costs, and improves the stability of material quality. At the same time, the two-step ball milling process of the present invention is low-energy ball milling, energy-saving and consumption-reducing, highly repeatable, convenient for actual production, and can be extended to the production of other heterogeneous composite materials.
[0039] The preparation method provided by the present invention is used to prepare high-strength and tough heterogeneous TiB w When preparing / TC4 composite materials, submicron TiB2 and TC4 raw material powders of different particle sizes are widely available and inexpensive, making them suitable for large-scale production.
[0040] The high-strength and tough heterogeneous TiB provided by the present invention w / TC4 composite material, with TC4 fine grains as the main matrix, has a heterogeneous configuration of TC4 coarse grain area and TC4 fine grain area in its microstructure. w It is a product of TiB2 and TC4 in situ self-generation; the reinforcement TiB wThe TiB is evenly distributed in the fine-grained area (distributed at the grain boundary and in the grain of the fine-grained area), and is distributed in a discontinuous ring shape at the boundary of the coarse-grained area. The coarse-grained area is evenly distributed on the fine-grained matrix, showing an obvious bimodal heterogeneous configuration. The microstructure can be adjusted by changing the coarse-grained content. The coarse-grained area and the fine-grained area in the organization are closely combined without an obvious separation interface. w The interface bonding between TC4 is excellent; the high-strength and tough heterogeneous TiB w / TC4 composite materials, while the strength is further improved, the plasticity of the material is synergistically improved, and the composite materials have more excellent comprehensive mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 TiB with heterogeneous structure w / Schematic diagram of the organizational structure of TC4 composite material;
[0042] Figure 2 This is a scanning electron microscope microscopic morphology photograph of the composite powder of TiB2+TC4 fine particles+TC4 coarse particles after two-step low-energy ball milling of the present invention;
[0043] Figure 3 The heterogeneous TiB prepared by the present invention w SEM microstructure of / TC4 composite material and TC4 coarse grain area and TiB w Energy spectrum of the enhancement body;
[0044] In the figure, Figure a is a scanning electron microscope microstructure photo of the composite material, Figure b is an enlarged view of the TC4 coarse grain area in Figure a, Figure c is an enlarged view of the boundary of the TC4 coarse grain area in Figure b, and Figure d is an enlarged view of the TiB w SEM microstructure photos of , Figure e is the energy spectrum scanning result of the cross point in Figure b, and Figure f is the energy spectrum scanning result of the cross point in Figure d;
[0045] Figure 4 TC4 fine-grained matrix alloy and TiB prepared by vacuum hot pressing w Room temperature tensile properties of / TC4 composites and photos of some tensile samples;
[0046] In the figure, Figure a is the tensile performance result diagram, and Figure b is a photo of the tensile sample of the composite material. DETAILED DESCRIPTION
[0047] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0048] In order to achieve the above object, the present invention provides the following specific implementation methods:
[0049] Embodiment 1: A method for preparing a high-strength and tough heterogeneous composite material, wherein the composite material is formed by titanium or titanium alloy as a titanium matrix and one or two of in-situ self-generated titanium carbide and titanium boride as a reinforcing phase; the method for preparing the titanium-based composite material comprises the following steps:
[0050] Step 1: subjecting a mixed powder of 1-3wt.% of reinforcing phase source powder and 97-99wt.% of titanium fine-grained matrix powder with a powder size of 1-45μm to at least one unidirectional non-stop low-energy ball milling treatment for 6-10 hours at a rotation speed of 180-220r / min to embed the reinforcing phase source into the surface of the titanium matrix to obtain a reinforcing phase source / titanium fine-grained matrix composite powder;
[0051] Among them, in the unidirectional non-stop low-energy ball milling process, stainless steel grinding balls with a diameter of 5 to 10 mm are used, and the ball-to-material ratio during the ball milling process is 3:1 to 5:1.
[0052] Step 2: Add 5-30wt.% of titanium coarse-grained matrix powder with a powder size of 120-280μm to the reinforcing phase source / titanium fine-grained matrix composite powder, and perform one-way non-stop low-energy ball milling for at least 1-4h at a speed of 80-120r / min to ensure the sphericity of the coarse-grained and fine-grained matrix powders while making the coarse-grained matrix powder evenly dispersed to obtain a reinforcing phase source / titanium fine / coarse-grained matrix composite powder;
[0053] Among them, in the unidirectional non-stop low-energy ball milling process, stainless steel grinding balls with a diameter of 5 to 10 mm are used, and the ball-to-material ratio during the ball milling process is 3:1 to 5:1.
[0054] Step 3: vacuum hot pressing and sintering the composite powder of the reinforcement phase source / titanium fine / coarse grain matrix in a mold, and opening the mold after sintering to obtain the high-strength and toughness heterogeneous reinforcement phase / titanium matrix composite material;
[0055] The mold is a graphite mold with a compressive strength greater than 60 MPa. At the same time, after the composite powder is loaded into the mold, cold pressing is performed at 5 to 15 MPa for 0.5 to 4 hours to make the composite powder dense and make the subsequent sintering pressurization more stable.
[0056] Vacuum hot pressing sintering is a process in which the composite powder in the mold is subjected to at least three-stage heating treatment from room temperature to 1100-1200°C at a pressure of 10-35MPa, a temperature of 1100-1200°C, and a heating rate of 5-10°C / min. The final process is to keep the temperature and pressure for 0.5-2h and then cool and unload the powder in the furnace.
[0057] The three-stage heating process of vacuum hot pressing sintering is specifically as follows:
[0058] First, heat from room temperature to 500-600°C, and keep at 500-600°C for 10-15 minutes;
[0059] Secondly, heat from 500-600℃ to 900-1000℃, and keep at 900-1000℃ for 10-15min.
[0060] Finally, heat from 900-1000℃ to 1100-1200℃, and keep at 1100-1200℃ for 0.5-2h, and cool with the furnace after heating;
[0061] At the same time, during the three-stage heating process, when the temperature rises to 500-600°C, the pressure is increased to 30-40% of the maximum pressure, when the temperature rises to 900-1000°C, the pressure is increased to 70-80% of the maximum pressure, and when the maximum temperature reaches 1100-1200°C, the pressure is increased to the maximum pressure of 10-35MPa. After maintaining the pressure, the furnace is cooled and unloaded.
[0062] Embodiment 2: Same as Embodiment 1, except that,
[0063] Step 3: spark plasma sintering the composite powder of the reinforcement phase source / titanium fine / coarse grain matrix in a mold, and opening the mold after sintering to obtain the high-strength and toughness heterogeneous reinforcement phase / titanium matrix composite material;
[0064] Spark plasma sintering is a process of at least three-stage heating of composite powder in a mold at a pressure of 20-50 MPa, a temperature of 1000-1200°C, and a heating rate of 20-100°C / min. The final heat and pressure maintenance is 0.2-1h and then the powder is unloaded from the furnace.
[0065] The three-stage heating process of spark plasma sintering is as follows:
[0066] First, heat from room temperature to 500-600°C, and keep at 500-600°C for 5-10 minutes;
[0067] Secondly, heat from 500-600℃ to 800-900℃, and keep at 800-900℃ for 5-10min.
[0068] Finally, heat from 800-900℃ to 1000-1200℃, and keep at 1000-1200℃ for 0.2-1h, and cool with the furnace after heating;
[0069] At the same time, during the three-stage heating process, the pressure is increased to 30-40% of the maximum pressure when the temperature rises to 500-600°C, and to 70-80% of the maximum pressure when the temperature rises to 800-900°C. When the maximum temperature reaches 1000-1200°C, the maximum pressure is increased to 20-50MPa. After maintaining the pressure, the furnace is cooled and unloaded, and the sintering atmosphere is vacuum.
[0070] Example 3: The same as Example 1, except that the reinforcing phase source is titanium diboride powder, the matrix is TC4 fine crystal and coarse grain powder, the obtained composite powder is a composite powder of TiB2 / TC4 titanium fine / coarse grain matrix, and the final composite material is a high-strength and tough heterogeneous TiB w / TC4 composite material; the particle size of the TiB2 is 0.5μm, the fine grain size of the TC4 powder is 1 to 25μm, the coarse grain size of the TC4 powder is 100 to 150μm, the TiB w It is in-situ self-generated titanium boride whisker.
[0071] Example 4: The same as Example 2, except that the reinforcing phase source is titanium diboride powder, the matrix is TC4 fine crystal and coarse grain powder, the obtained composite powder is TiB2 / TC4 titanium fine / coarse grain matrix composite powder, and the final composite material is high-strength and tough heterogeneous TiB w / TC4 composite material; the particle size of the TiB2 is 0.5μm, the fine grain size of the TC4 powder is 1 to 25μm, the coarse grain size of the TC4 powder is 100 to 150μm, the TiB w It is in-situ self-generated titanium boride whisker.
[0072] Example 5: The present invention also provides a high-strength and tough heterogeneous TiB obtained by the preparation method w / TC4 composite material, the TiB w The / TC4 composite material has a heterogeneous structure of TC4 coarse-grained region and TC4 fine-grained region. w It is a self-produced product of the in-situ reaction of TiB2 and TC4; the reinforcing phase TiB w It is dispersed and evenly distributed in the fine-grained area, distributed at the grain boundaries and inside the grains in the fine-grained area, distributed in discontinuous rings at the boundaries of the coarse-grained area, and the coarse-grained area is evenly distributed on the fine-grained matrix, showing an obvious bimodal heterogeneous configuration.
[0073] like Figures 1 to 4 To further illustrate the technical scheme and technical effects of the present invention, the following specific examples are provided:
[0074] Specific example 1: Figures 1 to 3 As shown, some of the raw materials used in the present invention come from the following sources:
[0075] 0.5μm grade titanium diboride (TiB2) powder was provided by Shanghai Buwei Applied Materials Technology Co., Ltd.;
[0076] 1~25μm grade TC4 (Ti6Al4V) fine spherical powder is provided by Ningbo Zhongyuan New Material Technology Co., Ltd.;
[0077] 100-150μm grade TC4 (Ti6Al4V) coarse spherical powder: Xi'an Ouzhong Materials Technology Co., Ltd.;
[0078] The above-mentioned 0.5 μm TiB2, 0-25 μm TC4 fine spherical powder and 100-150 μm TC4 coarse spherical powder were used as raw materials to prepare Heterogeneous TiB with a height of h = 10 mm w / TC4 composite block.
[0079] The theoretical density of TC4 is 4.44 g / cm 3 The theoretical density of TiB2 is 4.52 g / cm 3 According to the theoretical density formula of composite materials The theoretical density of the composite material can be calculated. When the content of titanium diboride increases from 1wt.% to 3wt.%, the TiB w The theoretical density of the TC4 composite material is 4.441 g / cm 3 Increased to 4.442g / cm 3 .
[0080] Since the theoretical density does not change much, the theoretical density of the composite material is taken as 4.44 g / cm 3 , and then according to the mass and density formula The total mass of powder required was calculated to be 125.47 g.
[0081] The specific preparation steps are as follows:
[0082] (1) Preparation of TiB2 / TC4 composite powder: 3 wt.% of titanium diboride and 97 wt.% of TC4 fine-grained matrix powder were weighed in a vacuum glove box. The sum of the mass percentages of the above two components was 100%.
[0083] After calculation, the TiB2 and TC4 fine powders are 3.39g and 109.53g respectively, totaling 112.92g. Then the weighed titanium diboride is mixed with the TC4 fine matrix powder, and the stainless steel balls and composite powder are sealed in a stainless steel ball mill according to a ball-to-material ratio (mass ratio) of 4:1;
[0084] (2) First step: low-energy ball milling: The ball mill was taken out of the vacuum glove box and placed on an omnidirectional planetary ball mill for 8 h of unidirectional low-energy ball milling at 200 rpm to ensure that the TiB2 particles were evenly distributed on the surface of the TC4 particles and that the TC4 particles had good sphericity;
[0085] (3) Second step of low-energy ball milling: Place the ball milling jar after the ball milling in step (2) in the vacuum glove box again, open the ball milling jar, and add 10wt.% TC4 coarse crystal powder to the composite powder in step (1) according to the required sample size and shape. After calculation, the amount of TC4 coarse powder added is 12.55g, and the sum of the mass of the coarse powder and the composite powder in step (1) is 125.47g, which is equal to the total mass of the required powder. Then add 50.2g of stainless steel balls to ensure that the total ball-to-material ratio in the ball milling jar is consistent, and seal the mixed powder and stainless steel balls in the stainless steel ball milling jar; then take out the ball milling jar from the glove box and perform one-way non-stop low-energy ball milling at 120rpm for 2h to ensure the sphericity of the coarse and fine crystal TC4 powders while making the TC4 coarse crystal powder evenly dispersed;
[0086] (4) Hot pressing and sintering: The ball milling jar after ball milling in step (3) is placed in a vacuum glove box, the powder is taken out, the powder is loaded into a high-strength graphite mold and hot pressed and sintered, and the mold is opened after sintering to obtain the high-strength and tough heterogeneous TiB w / TC4 composite material.
[0087] Wherein, in the step (4), after the composite powder is loaded into the graphite mold, it should be taken out from the vacuum glove box and cold pressed at 15 MPa for 1 hour to make the powder dense;
[0088] The specific hot pressing sintering process is: pressure 35MPa, temperature 1200℃, heating rate 10℃ / min, three-stage heating from room temperature to the highest temperature, first heating from room temperature to 600℃, keeping at 600℃ for 10min, then heating from 600℃ to 1000℃, keeping at 1000℃ for 10min, finally heating from 1000℃ to 1200℃ and keeping for 1h, cooling with the furnace after heating; during the three-stage heating process, the sintering pressure gradually increases, which are 10.5MPa and 24.5MPa respectively, and increases to 35MPa at 1200℃. After keeping the pressure for 1h, the furnace is cooled and unloaded, and the sintering atmosphere is vacuum.
[0089] The relative density and compactness of the sintered samples were measured using the Archimedean principle. The compactness of the above samples was 99.53%, which is extremely high. Among them, the TC4 fine-grained matrix alloy prepared by the process of this specific example and the uniform TiB without TC4 coarse grains w / TC4 composite material (100wt.%(fine grain + TiB w))The density of the samples are 99.88% and 99.92% respectively, and they also have dense tissues.
[0090] Scanning electron microscopy was used to test and characterize the surface of the composite powder after ball milling and the composite material sample after sintering.
[0091] in, Figure 1 TiB with heterogeneous structure w Schematic diagram of the organizational structure of the TC4 composite material, with the reinforcement TiB w It is dispersed and evenly distributed in the TC4 fine-grained area (both inside the crystal and at the grain boundary), and is distributed in a discontinuous ring shape at the boundary of the TC4 coarse-grained area. The coarse-grained area is distributed relatively evenly on the fine-grained matrix, showing an obvious bimodal heterogeneous configuration.
[0092] in, Figure 2 The scanning electron microscope microscopic morphology of the composite powder after two-step low-energy ball milling in this specific example can be observed from the figure that the TC4 coarse crystals have good sphericity and are relatively evenly dispersed, and the TC4 coarse crystal spherical powders are all attached with TC4 fine powders and TiB2. At the same time, there is no flat or broken powder in the field of view, and the sphericity of the TC4 fine powder is also good.
[0093] Figure 3 The heterogeneous TiB prepared in this specific example w SEM microstructure of the / TC4 composite material and the coarse grain area of TC4 and TiB w Energy spectrum of the enhanced body, from Figure 3 (ac) It can be clearly seen that the TiB is evenly distributed on the TC4 fine-grained matrix. w , the TiB is distributed in a discontinuous ring shape at the edge of the TC4 coarse grain zone w , and uniformly distributed circular TC4 coarse grain areas, any plane in three-dimensional space has this morphology. The two-level distribution of coarse and fine grain sizes is very obvious, and the bimodal heterogeneous configuration is reflected. There are no obvious defects such as pores and holes in the material, and the interface is tightly bonded.
[0094] Figure 3 (d) TiB can be observed w The morphology of TiB w The TiB grows to the interior of TC4 fine grains and grain boundaries, and the orientation is not uniform. This distribution makes the composite material isotropic. w It is formed in situ by itself. w It can be seen from the interface that the interface is clean, without defects such as cracks and holes, and has excellent interface bonding.
[0095] Figure 3 (ef) shows the interior of the TC4 coarse-grained region and the TiBw The energy spectrum scanning results show that the contents of titanium, aluminum and vanadium are high in the coarse grain area. w It contains almost only titanium and boron elements, and the energy spectrum point scanning results correspond to the microstructure.
[0096] Specific example 2:
[0097] Using the same raw material to prepare the diameter Heterogeneous TiB with a height of h = 15 mm w / TC4 composite block.
[0098] According to the mass and density formula The required amount of powder was calculated to be 188.21 g.
[0099] The specific steps are as follows:
[0100] (1) Preparation of TiB2 / TC4 composite powder: 3wt.% of titanium diboride and 97wt.% of TC4 fine-grained matrix powder were weighed in a glove box, and the sum of the mass percentages of the above two components was 100%. After calculation, the TiB2 and TC4 fine powders were 5.36g and 173.44g, respectively, for a total of 178.8g. The powders were then mixed, and the stainless steel balls and composite powder were sealed in a ball mill according to a ball-to-material ratio of 3:1;
[0101] (2) First step: low-energy ball milling: The ball mill is taken out of the vacuum glove box and placed on an omnidirectional planetary ball mill for unidirectional low-energy ball milling at 200 r / min for 10 h to ensure that the TiB2 particles are evenly distributed on the surface of the TC4 particles and that the TC4 particles have good sphericity;
[0102] (3) Second step of low-energy ball milling: Place the ball milling jar after the ball milling in step (2) in the vacuum glove box again, open the ball milling jar, and add 5wt.% TC4 coarse crystal powder to the composite powder in step (1) according to the required sample size and shape. After calculation, the amount of TC4 coarse powder added is 9.41g, and the sum of the mass of the coarse powder and the composite powder in step (1) is 188.21g, which is equal to the total mass of the required powder. Then add 28.23g of stainless steel balls to ensure the consistency of the total ball-to-material ratio in the ball milling jar, and seal the mixed powder and stainless steel balls in the stainless steel ball milling jar; then take out the ball milling jar from the glove box and perform one-way low-energy ball milling at 120r / min for 4h to ensure the sphericity of the coarse and fine crystal TC4 powders while making the TC4 coarse crystal powder uniformly dispersed;
[0103] (4) Hot pressing and sintering: The ball milling jar after ball milling in step (3) is placed in a vacuum glove box, the powder is taken out, and the powder is loaded into a high-strength graphite mold and hot pressed to sinter the powder to prepare a high-strength and tough heterogeneous TiB w / TC4 composite material.
[0104] Wherein, in step (4), after the composite powder is loaded into the graphite mold, it should be taken out from the vacuum glove box and cold pressed at 15 MPa for 1 h to make the powder dense;
[0105] The specific hot pressing sintering process is: pressure 30MPa, temperature 1200℃, heating rate 10℃ / min, three-stage heating from room temperature to the highest temperature, first heating from room temperature to 600℃, keeping at 600℃ for 10min, then heating from 600℃ to 1000℃, keeping at 1000℃ for 10min, finally heating from 1000℃ to 1200℃ and keeping for 1h, cooling with the furnace after heating; during the three-stage heating process, the sintering pressure gradually increases to 12MPa and 24MPa respectively, and increases to 30MPa at 1200℃. After keeping the pressure for 1h, the furnace is cooled and unloaded, and the sintering atmosphere is vacuum.
[0106] Specific example 3:
[0107] The same raw materials were used to prepare a disc-shaped heterogeneous TiB with a diameter of 60 mm and a height of 12 mm. w / TC4 composite block.
[0108] According to the mass and density formula The required amount of powder was calculated to be 150.57 g.
[0109] The specific steps are as follows:
[0110] (1) Preparation of TiB2 / TC4 composite powder: 3wt.% of titanium diboride and 97wt.% of TC4 fine-grained matrix powder were weighed in a glove box, and the sum of the mass percentages of the above two components was 100%. After calculation, the TiB2 and TC4 fine powders were 3.61g and 116.85g, respectively, for a total of 120.46g. The powders were then mixed, and the stainless steel balls and composite powder were sealed in a ball mill according to a ball-to-material ratio of 3:1;
[0111] (2) First step: low-energy ball milling: The ball mill is taken out of the vacuum glove box and placed on an omnidirectional planetary ball mill for unidirectional low-energy ball milling at 200 r / min for 6 h to ensure that the TiB2 particles are evenly distributed on the surface of the TC4 particles and that the TC4 particles have good sphericity;
[0112] (3) Second step of low-energy ball milling: Place the ball milling jar after the ball milling in step (2) in the vacuum glove box again, open the ball milling jar, and add 20wt.% TC4 coarse crystal powder to the composite powder in step (1) according to the required sample size and shape. After calculation, the amount of TC4 coarse powder added is 30.11g, and the sum of the mass of the coarse powder and the composite powder in step (1) is 150.57g, which is equal to the total mass of the required powder. Then add 90.33g of stainless steel balls to ensure the consistency of the total ball-to-material ratio in the ball milling jar, and seal the mixed powder and stainless steel balls in the stainless steel ball milling jar; then take out the ball milling jar from the glove box and perform one-way low-energy ball milling at 120r / min for 3h without stopping, to ensure the sphericity of the coarse and fine crystal TC4 powders while making the TC4 coarse crystal powder evenly dispersed;
[0113] (4) Hot pressing and sintering: The ball milling jar after ball milling in step (3) is placed in a vacuum glove box, the powder is taken out, and the powder is loaded into a high-strength graphite mold and hot pressed to sinter the powder to prepare a high-strength and tough heterogeneous TiB w / TC4 composite material.
[0114] In step (4), after the composite powder is loaded into the graphite mold, it should be taken out of the vacuum glove box and cold pressed at 15 MPa for 2 h to make the powder dense;
[0115] Furthermore, the hot pressing sintering process in step (4) is as follows: pressure 35 MPa, temperature 1150°C, heating rate 10°C / min, three-stage heating from room temperature to the highest temperature, firstly heating from room temperature to 600°C, keeping at 600°C for 10 min, then heating from 600°C to 1000°C, keeping at 1000°C for 10 min, finally heating from 1000°C to 1150°C, keeping at 1150°C for 1 h, and cooling with the furnace after heating is completed; during the three-stage heating process, the sintering pressure gradually increases to 14 MPa and 28 MPa, respectively, and increases to 35 MPa at 1150°C. After keeping the pressure for 1 h, the furnace is cooled and unloaded, and the sintering atmosphere is vacuum.
[0116] Specific example 4: Figure 4 As shown,
[0117] The same raw materials were used to prepare a disc-shaped heterogeneous TiB with a diameter of 55 mm and a height of 8 mm. w / TC4 composite block.
[0118] According to the mass and density formula The required amount of powder was calculated to be 84.35 g.
[0119] The specific steps are as follows:
[0120] (1) Preparation of TiB2 / TC4 composite powder: 3wt.% of titanium diboride and 97wt.% of TC4 fine-grained matrix powder were weighed in a glove box, and the sum of the mass percentages of the above two components was 100%. After calculation, the TiB2 and TC4 fine powders were 1.77g and 57.27g, respectively, for a total of 59.04g. The powders were then mixed, and the stainless steel balls and composite powder were sealed in a ball mill according to a ball-to-material ratio of 5:1;
[0121] (2) First step: low-energy ball milling: The ball mill is taken out of the vacuum glove box and placed on an omnidirectional planetary ball mill for unidirectional low-energy ball milling at 200 r / min for 8 h to ensure that the TiB2 particles are evenly distributed on the surface of the TC4 particles and that the TC4 particles have good sphericity;
[0122] (3) Second step of low-energy ball milling: Place the ball milling jar after the ball milling in step (2) in the vacuum glove box again, open the ball milling jar, and add 30wt.% TC4 coarse crystal powder to the composite powder in step (1) according to the required sample size and shape. After calculation, the amount of TC4 coarse powder added is 25.31g, and the sum of the mass of the coarse powder and the composite powder in step (1) is 84.35g, which is equal to the total mass of the required powder. Then add 126.55g of stainless steel balls to ensure the consistency of the total ball-to-material ratio in the ball milling jar, and seal the mixed powder and stainless steel balls in the stainless steel ball milling jar; take out the ball milling jar from the glove box, and perform one-way low-energy ball milling at 120r / min for 2h to ensure the sphericity of the coarse and fine crystal TC4 powders while making the TC4 coarse crystal powder uniformly dispersed;
[0123] (4) Hot pressing and sintering: The ball milling jar after ball milling in step (3) is placed in a vacuum glove box, the powder is taken out, and the powder is loaded into a high-strength graphite mold and hot pressed to sinter the powder to prepare a high-strength and tough heterogeneous TiB w / TC4 composite material.
[0124] In step (4), after the composite powder is loaded into the graphite mold, it should be taken out of the vacuum glove box and cold pressed at 10 MPa for 1 h to make the powder dense;
[0125] Furthermore, the hot pressing sintering process in step (4) is as follows: pressure 35 MPa, temperature 1100°C, heating rate 10°C / min, three-stage heating from room temperature to the highest temperature, firstly heating from room temperature to 600°C, keeping at 600°C for 10 min, then heating from 600°C to 1000°C, keeping at 1000°C for 10 min, finally heating from 1000°C to 1100°C, keeping at 1100°C for 1 h, and cooling with the furnace after heating is completed; during the three-stage heating process, the sintering pressure gradually increases to 10.5 MPa and 24.5 MPa, respectively, and increases to 35 MPa at 1100°C. After keeping the pressure for 1 h, the furnace is cooled and unloaded, and the sintering atmosphere is vacuum.
[0126] Among the mechanical property tests of metal structural materials, tensile property tests are considered to be the most important static strength test category. The tensile strength and elongation of composite materials are measured on a universal testing machine at a tensile rate of 0.6 mm / min.
[0127] Figure 4 The TC4 fine-grained matrix alloy and TiB prepared in Examples 1 to 4 w / TC4 composite material room temperature tensile performance results and some tensile sample photos, observation Figure 4 (a) It can be seen that compared with the TC4 fine-grained matrix, the 100wt.% (fine-grained + TiB w ) The uniform composite material has a strength of 1162MPa, but the fracture strain is 1.98% and the elongation is only 1%. The introduction of coarse grains, that is, the introduction of heterogeneous configuration, allows the composite material to maintain a high tensile strength while doubling its plasticity.
[0128] Figure 4 The numbers 4 to 6 represent heterogeneous TiB w The tensile strength and plasticity of the / TC4 composite material are improved to varying degrees compared with the TC4 matrix, achieving a synergistic increase in material strength and plasticity, especially the 90wt.% (fine grain + TiB w )-10wt.% coarse-grained heterogeneous structural composite material has a tensile strength of 1133MPa and an elongation of 4.48%, which are 18.3% and 14.9% higher than those of TC4 matrix, respectively, and has the best strength and plasticity matching. This shows that the heterogeneous structure TiB w / TC4 composite materials have outstanding comprehensive mechanical properties.
[0129] Specific example 5:
[0130] Specific Example 5 is prepared in the same manner as Specific Example 1, except that:
[0131] Step (1) In a glove box, weigh 2 wt.% of titanium diboride and 98 wt.% of TC4 fine-grained matrix powder. The sum of the mass percentages of the above two components is 100%. After calculation, the TiB2 and TC4 fine powders are 2.26 g and 110.66 g respectively, totaling 112.92 g.
[0132] Step (3) taking out the ball mill from the glove box and performing unidirectional low-energy ball milling at 120 r / min for 1 h to ensure the sphericity of the coarse-grained and fine-grained TC4 powders while making the TC4 coarse-grained powder evenly dispersed;
[0133] In step (4), the hot pressing sintering pressure is 25 MPa, the heating rate is 5°C / min, and the sintering pressure is gradually increased during the three-stage heating process, reaching 25 MPa at 1200°C. After keeping the temperature and pressure for 1 hour, the furnace is cooled and unloaded, and the sintering atmosphere is vacuum.
[0134] Specific Example 6:
[0135] Specific Example 6 is prepared in the same manner as Specific Example 1, except that:
[0136] Step (1) In a glove box, weigh 1wt.% of titanium diboride and 99wt.% of TC4 fine-grained matrix powder. The sum of the mass percentages of the above two components is 100%. After calculation, the TiB2 and TC4 fine powders are 1.13g and 111.79g respectively, totaling 112.92g.
[0137] Step (3) taking out the ball mill from the glove box and performing unidirectional low-energy ball milling at 120 r / min for 3 h to ensure the sphericity of the coarse-grained and fine-grained TC4 powders while making the TC4 coarse-grained powder evenly dispersed;
[0138] Step (4) performs spark plasma sintering, the sintering temperature is 1100°C, the heating rate is 50°C / min, and three-stage heating is adopted from room temperature to the highest temperature, firstly heating from room temperature to 600°C, keeping at 600°C for 15min, then heating from 600°C to 1000°C, keeping at 1000°C for 15min, and finally heating from 1000°C to 1100°C, and cooling with the furnace after heating is completed; during the three-stage heating process, the sintering pressure is gradually increased, and is increased to 40MPa at 1100°C. After keeping the temperature and pressure for 1h, the furnace is cooled and unloaded, and the sintering atmosphere is vacuum.
[0139] The above description is only a preferred specific example of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-strength and high-toughness heterogeneous composite material, characterized in that: The composite material is formed by titanium or titanium alloy as a titanium matrix and one or two of in-situ self-generated titanium carbide and titanium boride as a reinforcing phase; the preparation method of the titanium-based composite material comprises the following steps: A mixed powder of a reinforcing phase source material powder with a mass percentage of 1 to 3 wt.% and a titanium fine-grained matrix powder with a corresponding mass percentage of 97 to 99 wt.% and a powder size of 1 to 45 μm is subjected to at least one unidirectional non-stop low-energy ball milling treatment for 6 to 10 hours at a rotation speed of 180 to 220 r / min to embed the reinforcing phase source into the surface of the titanium powder particles to obtain a reinforcing phase source / titanium fine-grained matrix composite powder; Next, a titanium coarse-grained matrix powder with a mass percentage of 5 to 30 wt.% and a powder size of 120 to 280 μm is added to the reinforcing phase source / titanium fine-grained matrix composite powder, and a one-way non-stop low-energy ball milling treatment is performed at least once for 1 to 4 hours at a rotation speed of 80 to 120 r / min to ensure the sphericity of the coarse-grained and fine-grained matrix powders while uniformly dispersing the coarse-grained matrix powder to obtain a reinforcing phase source / titanium fine / coarse-grained matrix composite powder; Finally, the composite powder of the reinforcement phase source / titanium fine / coarse grain matrix is subjected to vacuum hot pressing sintering or spark plasma sintering in a mold. After sintering, the mold is opened to obtain the high-strength and toughness heterogeneous reinforcement phase / titanium matrix composite material.
2. The high-strength and toughness heterogeneous composite material and the preparation method thereof according to claim 1, characterized in that: In the one-way non-stop low-energy ball milling process, stainless steel grinding balls with a diameter of 5 to 10 mm are used, and the ball-to-material ratio in the two ball milling processes is 3:1 to 5:
1.
3. The high-strength and toughness heterogeneous composite material and the preparation method thereof according to claim 1, characterized in that: The mold is a graphite mold with a compressive strength greater than 60MPa.
4. The high-strength and toughness heterogeneous composite material and the preparation method thereof according to claim 1, characterized in that: After the composite powder is loaded into the mold, cold pressing is performed at 5 to 15 MPa for 0.5 to 4 hours to make the composite powder dense and air-free, the powder not easily oxidized, and the subsequent sintering and pressurizing process more stable.
5. The high-strength and toughness heterogeneous composite material and the preparation method thereof according to claim 1, characterized in that: The vacuum hot pressing sintering is a process in which the composite powder in the mold is subjected to at least three-stage heating treatment from room temperature to 1100-1200°C under the conditions of a pressure of 10-35MPa, a temperature of 1100-1200°C, and a heating rate of 5-10°C / min, and finally the composite powder is kept at temperature and pressure for 0.5-2h and then unloaded by furnace cooling.
6. The high-strength and toughness heterogeneous composite material and the preparation method thereof according to claim 5, characterized in that: The three-stage heating process of vacuum hot pressing sintering is specifically as follows: First, heat from room temperature to 500-600°C, and keep at 500-600°C for 10-15 minutes; Secondly, heat from 500-600℃ to 900-1000℃, and keep at 900-1000℃ for 10-15min. Finally, heat from 900-1000℃ to 1100-1200℃, and keep at 1100-1200℃ for 0.5-2h, and cool with the furnace after heating; At the same time, during the three-stage heating process, when the temperature rises to 500-600°C, the pressure is increased to 30-40% of the maximum pressure, when the temperature rises to 900-1000°C, the pressure is increased to 70-80% of the maximum pressure, and when the maximum temperature reaches 1100-1200°C, the pressure is increased to the maximum pressure of 10-35MPa. After maintaining the pressure, the furnace is cooled and unloaded.
7. The high-strength and toughness heterogeneous composite material and the preparation method thereof according to claim 1, characterized in that: The spark plasma sintering is a process of at least three-stage heating of the composite powder in the mold under the conditions of a pressure of 20-50 MPa, a temperature of 1000-1200° C., and a heating rate of 20-100° C. / min, and finally heat-maintaining and pressure-maintaining for 0.2-1 h before being unloaded from the furnace.
8. The high-strength and toughness heterogeneous composite material and the preparation method thereof according to claim 7, characterized in that: The three-stage heating process of spark plasma sintering is specifically as follows: First, heat from room temperature to 500-600°C, and keep at 500-600°C for 5-10 minutes; Secondly, heat from 500-600℃ to 800-900℃, and keep at 800-900℃ for 5-10min. Finally, heat from 800-900℃ to 1000-1200℃, and keep at 1000-1200℃ for 0.2-1h, and cool with the furnace after heating; At the same time, during the three-stage heating process, the pressure is increased to 30-40% of the maximum pressure when the temperature rises to 500-600°C, and to 70-80% of the maximum pressure when the temperature rises to 800-900°C. When the maximum temperature reaches 1000-1200°C, the maximum pressure is increased to 20-50MPa. After maintaining the pressure, the furnace is cooled and unloaded, and the sintering atmosphere is vacuum.
9. The high-strength and toughness heterogeneous composite material and the preparation method thereof according to any one of claims 1 to 8, characterized in that: The reinforcing phase source is titanium diboride powder, the matrix is TC4 fine crystal and coarse grain powder, the obtained composite powder is TiB2 / TC4 titanium fine / coarse grain matrix composite powder, and the final composite material is high-strength and tough heterogeneous TiB w / TC4 composite material; the particle size of the TiB2 is 0.5μm, the fine grain size of the TC4 powder is 1 to 25μm, the coarse grain size of the TC4 powder is 100 to 150μm, the TiB w It is in-situ self-generated titanium boride whisker.
10. A high-strength and tough heterogeneous TiB prepared by the preparation method of claim 9 w / TC4 composite material, characterized in that The TiB w The / TC4 composite material has a heterogeneous structure of TC4 coarse-grained region and TC4 fine-grained region. w The particles are self-produced by in-situ reaction of TiB2 and TC4; the reinforcing phase TiB w It is dispersed and evenly distributed in the fine-grained area, distributed at the grain boundaries and inside the grains in the fine-grained area, distributed in discontinuous rings at the boundaries of the coarse-grained area, and the coarse-grained area is evenly distributed on the fine-grained matrix, showing an obvious bimodal heterogeneous configuration.
Citation Information
Patent Citations
A titanium-based composite material with a heterogeneous structure, its preparation method and application
CN111961902B
A three-dimensional pellet composite TiB-reinforced TMCs and its preparation method
CN112647029B
A titanium alloy-based composite material with microstructure and its preparation method
CN112695262B